(untitled) - H Kim Lew ...[et al.] (Indianapolis, Indiana, 1999)
The book provides the informationnecessary to troubleshoot many problems commonly encoutered in internetworks using Cisco hardware and software products
Keywords: internet working ( telecommunication - handbooks, manuals,etc. )